Middle school curriculum, instruction, and assessment - Anfara, Vincent A.; Stacki, Sandra L. (Emerald Publishing Limited : Information Age, 2002)
This handbook explores the curriculum, instruction and assessment used in middle schools. The essays cover: curriculum integration - history and research; the relationship between middle grades teacher certification and teaching practices; and cohorts in middle level teacher preparation.
Keywords: Middle school teaching -- United States.; Middle schools -- United States.; Educational change -- United States.; Education -- Curricula.; Primary and middle schools.; Curriculum planning and development.; elektronické knihy; electronic books